2017
DOI: 10.9775/kvfd.2017.18529
|View full text |Cite
|
Sign up to set email alerts
|

Pelet ve Ekstrude Mamaların Köpek Beslemede Kullanılması

Abstract: This study was carried out to determine the effects of pellet and extruded foods on gelatinization, digestibility and faecal quality of dogs. In study 30 adult male dogs of mixed breed, weighing 15-30 kg, neutered and around 1-3 of age were used. The two tested dog-food formulations had the same composition, but one was produced in pellet form, while the other was extruded in a private factory. Feeding experiments were conducted at the Dog Unit of the Veterinary Faculty in Selçuk University. Pelleted and extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Therefore, small amounts of gelatinization are inevitable as moisture is added ( Lewis et al, 2015 ). İnal et al (2018) produced a same-recipe dog food through extrusion and pelleting, and like the present study, they found that extrusion resulted in at least four times more gelatinization than pelleting. Had they ( İnal et al, 2018 ) produced a baked biscuit, they might have seen similar results to the present study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, small amounts of gelatinization are inevitable as moisture is added ( Lewis et al, 2015 ). İnal et al (2018) produced a same-recipe dog food through extrusion and pelleting, and like the present study, they found that extrusion resulted in at least four times more gelatinization than pelleting. Had they ( İnal et al, 2018 ) produced a baked biscuit, they might have seen similar results to the present study.…”
Section: Discussionsupporting
confidence: 83%
“… İnal et al (2018) produced a same-recipe dog food through extrusion and pelleting, and like the present study, they found that extrusion resulted in at least four times more gelatinization than pelleting. Had they ( İnal et al, 2018 ) produced a baked biscuit, they might have seen similar results to the present study. During baking, the water is limited and the biscuit is cooked through convection, radiation, and conduction ( Sakin et al, 2009 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Milder cooking processes like baking and pelleting of kibbles have been reported to result in less starch gelatinization when comparing the same extruded recipe ( Inal et al 2018;Gibson and Alavi 2013). Pelleting is not a common process for dog food and pellets have been reported to be less palatable than extruded kibbles ( Inal et al 2018). This is likely because of the lower starch gelatinization and different texture of pellets.…”
Section: Processing Of Pet Foods With Cornmentioning
confidence: 99%
“…The highest digestibility was determined in CG sucuk foods. Dogs eat and digest diets that high in heat-treated starch (29,2). It has been determined in previous studies that the OM digestibility rate of cooked starch in dogs is very high (7,39).…”
Section: Discussionmentioning
confidence: 99%